P025: Checking the pulse in the 21st century: inter-observer reliability of carotid pulse detection by point-of-care ultrasound. (May 2020) - Smith, D.; Chenkin, J.; Simard, R.
Abstract : Introduction: Detection of a pulse is crucial to decision-making in the care of patients who are in cardiac arrest, however, the current standard of manual pulse palpation is unreliable. An emerging alternative is the use of point-of-care ultrasound (POCUS) for direct assessment of the carotid pulse. The primary objective of this study is to determine the inter-observer reliability for healthcare provider interpretation of the carotid pulse by POCUS in patients who are peri-arrest or in cardiac arrest. Methods: We conducted a web-based survey of healthcare providers. Participants were shown a tutorial demonstrating POCUS detection of the carotid pulse and then asked to interpret 15 carotid pulse ultrasound clips from patients who were peri-arrest or in cardiac arrest. The primary outcome was inter-observer reliability for carotid pulse assessment. Secondary outcomes included inter-observer reliability stratified by healthcare provider role and POCUS experience, mean tutorial duration, mean pulse assessment duration, rate of pulse assessments < 10 seconds, and change in participant confidence before and after the study. Inter-observer reliability was determined by Krippendorff's α. Change in participant confidence was determined by Wilcoxon signed-rank test. Results: 68 participants completed our study, with a response rate of 75% (68/91). There was near perfect inter-observer reliability for pulse assessment amongst all study participants (α=0.874, 95% CI 0.869, 0.879). Senior residents (n = 24) and POCUS experts (n = 6) demonstrated the highest rates of inter-observer reliability, α=0.902 (95% CI 0.888, 0.914) and α=0.925 (95% CI 0.869, 0.972), respectively. All sub-groups had α greater than 0.8. Mean tutorial duration was 31 seconds (SD = 17.5) with maximum duration of 55 seconds. Mean pulse assessment duration was 7.7 seconds (SD = 5.2) with 76% of assessments completed within 10 seconds. Participant confidence before and after the study significantly increased from a median of 2 to a median of 4 on a 5-point Likert-type scale (z = 6.3, p < .001). Conclusion: Interpretation of the carotid pulse by POCUS showed near perfect inter-observer reliability for patients who were peri-arrest or in cardiac arrest. Participants required minimal training and indicated improved POCUS pulse assessment confidence after the study. Further work must be done to determine the impact of POCUS pulse assessment on the resuscitation of patients in cardiac arrest.